2022
DOI: 10.1186/s12951-022-01680-7
|View full text |Cite
|
Sign up to set email alerts
|

From nanoparticles to crystals: one-pot programmable biosynthesis of photothermal gold structures and their use for biomedical applications

Abstract: Inspired by nature, green chemistry uses various biomolecules, such as proteins, as reducing agents to synthesize metallic nanostructures. This methodology provides an alternative route to conventional harsh synthetic processes, which include polluting chemicals. Tuning the resulting nanostructure properties, such as their size and shape, is challenging as the exact mechanism involved in their formation is still not well understood. This work reports a well-controlled method to program gold nanostructures' sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…It should be noted that the NPs formation kinetics could be expedited (to 2–3 hours) by heating the solution to 70 °C, as was established in a previous paper. 35…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the NPs formation kinetics could be expedited (to 2–3 hours) by heating the solution to 70 °C, as was established in a previous paper. 35…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the NPs formation kinetics could be expedited (to 2-3 hours) by heating the solution to 70 °C, as was established in a previous paper. 35 It was observed that the mixed-metal solution, after a few hours from the addition of mucin, changed in color from light yellow to light red, similar to the solution with Au in Environmental Science: Nano Paper isolation. This observation again indicates the formation of Au NPs with mucin's assistance.…”
Section: Gold Adsorption and Recovery By Mucinmentioning
confidence: 91%
See 2 more Smart Citations
“…Examples include Au, Ag and even complex metal-insulator structures. [32][33][34][35][36][37][38] Mucin glycoproteins belong to a large family of mucus proteins, 39 a complex viscous adherent secretion synthesized by specialized goblet cells in the epithelium for shielding functions. These cell lines are present in organs exposed to the external environment, including the respiratory, gastrointestinal, and reproductive tracts.…”
Section: Introductionmentioning
confidence: 99%